Game : ompeting in Africa's playing fields - Townsend, Stephanie; Luiz, John ([London] : SAGE, 2016)
In 2007, Jan Potgieter, chief executive of Massdiscounters, a division of Massmart, had steered Game, one of its general merchandise discounters, into investing far more vigorously in Africa. By June 2010, Game had shown significant growth in both turnover and profit, but Potgieter wanted the company's operations in Africa to become even stronger. This book explains how the company planned for the arrival of new players entering the African market.
Originally Published in: Townsend, S., & Luiz, J. (2010). Game: Competing in Africa's Playing Fields. WBS-2010-9. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Game (Firm); Strategic planning -- Case studies; Organizational change -- Case studies